Treatment of traumatic coxofemoral luxation with triple pelvic osteotomy in 19 dogs (1987-1999) - Haburjak, J. J.; Lenehan, T. M.; Harari, J.; Gurevitch, R.; Rivers, B.; Tarvin, G. B.; Constable, P. D. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
The objective of our study was to investigate, retrospectively, the role of triple pelvic osteotomy in the management of traumatic coxofemoral luxation. Nineteen patients were identified from medical record data and four dogs returned for long-term physical, goniometric and radiographic evaluation. Seventeen of nineteen dogs had maintenance of reduction of the hip. Due to poor outcome, two of these seventeen dogs required salvage procedures. Three of four dogs that returned for long-term follow-up, owner evaluation, radiographic scoring, and physical examination had satisfactory results. These four dogs had manual goniometric evaluations performed on the affected side, and the contralateral hip. A paired student t-test was used for statistical analysis, and internal rotation was the only value which was significantly (p d0.05) different between the two sides. Reduction alone is not a representation of success when evaluating open management of coxofemoral luxation, because two dogs with poor limb function necessitated femoral head and neck excision for limb salvage. The TPO does have a role in the treatment of traumatic coxofemoral luxation, but may not be sufficient in cases involving congenital dysplasia and/or intraarticular fractures.Triple pelvic osteotomy is a successful means of mitigating the sequela of congenital hip subluxation. This surgical technique can be used to manage dogs with traumatic coxofemoral luxation. There was an indication in this study that reduction alone is not a satisfactory means of evaluating management of traumatic coxofemoral luxation. Dogs with congenital dysplasia or intra-articular fractures associated with traumatic luxation may require alternate methods of reduction.
Keywords: TPO; traumatic hip luxation; open reduction